Determinants of the intrahousehold allocation of food in the rural Philippines - Senauer, Benjamin; Garcia, Marito; Jacinto, Elizabeth (Wiley, 1988)
This study shows that the opportunity cost of time for husbands and wives can affect the intrahousehold distribution of food in a developing country. Equations which explain the relative allocation of calories within households were estimated for husbands, wives, and children with data for the rural Philippines. The estimating equation is derivable from both a joint household utility function and a bargaining model. Because the same households were included in the four survey rounds, the various observations for a given individual were averaged for each variable in the estimation procedure. Wages were estimated using the Heckman approach.